IMPACT OF IRON SUPPLEMENT TABLET COMPLIANCE ON HEMOGLOBIN LEVELS IN PREGNANT WOMEN - Ramadhani, Juwita; Hasniah; Anggi Saputri, Mutiara (Bajang Institute, 2025)
Iron Supplement Tablets (IST) are utilized to facilitate biological processes in the human body, particularly in hemoglobin synthesis, since the body requires iron minerals from these tablets. IST has 60 mg of iron (in the forms of Ferro Sulfate, Ferro Fumarate, or Ferro Gluconate) and 0.400 mg of Folic Acid. Administering iron supplementation therapy to pregnant women is one of the most effective methods to prevent and address nutritional anemia by elevating hemoglobin levels. This study aimed to assess the impact of adherence to IST consumption and the factors influencing hemoglobin levels in pregnant women. This research employs a quantitative methodology with a prospective design. This study employs a cross-sectional approach, wherein data is collected simultaneously during the distribution of the MARS-5 questionnaire scale. The population of 429 was determined using the Lemes Show formula, yielding 60 respondents. The results indicated that among 60 respondents, compliance among pregnant women was high (1.7%), moderate (90%), and low (8.3%). The study findings indicate that among pregnant women, 41.7% exhibited normal hemoglobin levels, 28.3% had mild anemia, 18.3% presented with moderate anemia, and 8.3% experienced severe anemia. The findings of this study indicated the impact of adherence to IST consumption on hemoglobin levels, with a chi-square test yielding a P-value of (<0.001). Additionally, parity factors influenced compliance with IST consumption, as evidenced by a chi-square test resulting in a P-value of (0.010).